GIS AND LANDSCAPE ANALYSIS - Pandolfi, Alessandra; Campi, Paola; Terlizzi, Luca (PEOPLE: International Journal of Social Sciences, 2017)
Landscape is “an area, as perceived by people, whose character is the result of the action and interaction of natural and/or human factors” (Council of Europe, European Landscape Convention, 2000). The changing conditions of this complex factor, that determines the variability of our local and national contexts in Europe, can be effectively measured thanks to quantitative and qualitative indicators. These values could be calculated through procedures implemented thanks to Geographical information systems (GIS), using elements of geostatistics and numeric cartography. The speculative basics of the need of using GIS for the landscape analysis is strongly connected to the necessity of finding a steadier definition of its variability in time and space, mainly in a context like the European Union, that is in constant demand for procedures that could be standardized as best practices.